High Performance Polymers and Their Nanocomposites - P. M., Visakh (John Wiley & Sons, Incorporated, 2018)
High Performance Polymers and Their Nanocomposites summarizes many of the recent research accomplishments in the area of high performance polymers, such as: high performance polymers-based nanocomposites, liquid crystal polymers, polyamide 4, 6, polyamideimide, polyacrylamide, polyacrylamide-based composites for different applications, polybenzimidazole, polycyclohexylene dimethyl terephthalate, polyetheretherketone, polyetherimide, polyetherketoneketone, polyethersulfone, polyphenylene sulphide, polyphenylsulfone, polyphthalamide, Polysulfone, self-reinforced polyphenylene, thermoplastic polyimide.